Validation method for determining sodium benzoate in fruit juice drinks in Malang - Engrid Juni Astuti; Roha Fakhri Naufal Ilham; Januar Rahman (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2019)
Sodium benzoate is a preservative that is permitted to be used in food and beverages. The maximum limit for using sodium benzoate in food is 600 mg/L of ingredients calculated as benzoic acid. In this study, High-Performance Liquid Chromatography (HPLC) method using a PDA detector was used for sodium benzoate levels analysis in fruit juice drink circulating in Malang. The mobile phase composition used in this study was methanol pro-HPLC:aqua pro injection (70:30) and added glacial acetic acid to reach pH 3. The analysis was conducted at a wavelength of 245 nm, and the flow rate was set at 1.00 mL/minute. This method was validated against the parameters of selectivity, linearity, accuracy, and precision, and the results obtained to meet the validation requirements. The application of the HPLC method after being validated in the determination of sodium benzoate levels in fruit juice drink circulating in Malang resulted in selectivity Rs ≥ 1.5, linearity obtained in the range 0.1-5 μg/mL with a correlation coefficient (r) = 0,9999, recovery at a concentration of 80%, 100%, and 120% was 105.31%, and precision with an RSD value of 1.40%. Based on the results, it can be concluded that the validation method of analysis shows that the method can be used to determine sodium benzoate level using HPLC with PDA detectors for routine use in fruit juice drink samples.